Release of TiO2 nanoparticles from painted surfaces in cold climates: characterization using a high sensitivity single-particle ICP-MS. Issue 1 (23rd December 2019) - Azimzada, Agil; Farner, Jeffrey M.; Hadioui, Madjid; Liu-Kang, Carolyn; Jreije, Ibrahim; Tufenkji, Nathalie; Wilkinson, Kevin J.
Abstract : Wet, cold or freeze-thaw conditions enhanced the release of TiO2 nanoparticles from outdoor painted surfaces. Abstract : Paints and coatings represent one of the major applications of TiO2 nanoparticles (NPs). While it has been previously shown that NPs are released from painted surfaces, there is still a lack of experimental data on their release rates under natural conditions and on the size distributions of the NPs following release. This study quantifies TiO2 NP release from painted surfaces under natural weathering conditions and identifies the main seasonal factors that contribute to increased NP release. First, an analytical methodology using a highly sensitive single particle inductively coupled plasma mass spectrometer (SP-ICP-MS) was developed that improved the size detection limit (SDL) of the technique down to <20 nm for TiO2 NPs. Precipitation (rain, snow) was collected after it came into contact with painted panels that were exposed to natural weathering. NPs that were released from the paint, as well as those pre-existing in the precipitation were thoroughly characterized with respect to their size distributions, particle number concentrations and total metal content. During the 10 week winter exposure, 3 × 10 11 NP per m 2 were released, corresponding to <0.001% of the TiO2 NP load on the panels, with most of the NPs found in the 20–60 nm range. Significantly fewer NPs were released during the summer than the winter, in spite of the fact that there was more precipitation in the summer. Controlled lab weathering experiments revealed that NP release was significantly enhanced for wet surfaces, particularly, when the samples underwent freeze–thaw cycles. The results also indicated that NP release and loss ( i.e. through agglomeration, sedimentation or sorption, etc. ) are dynamic processes that are a function of the physical and chemical properties of the external medium. Although NP release is a primary determinant in environmental risk, subsequent NP behavior leading to losses or re-suspension can be equally critical.